Prevalence and prognosis of lead masses in patients with cardiac implantable electronic devices without infection. Issue 6 (June 2019) - Golzio, Pier Giorgio; Errigo, Daniele; Peyracchia, Mattia; Gallo, Elisa; Frea, Simone; Castagno, Davide; Budano, Carlo; Giustetto, Carla; Rinaldi, Mauro
Abstract : Background: Finding of intracardiac lead masses in patients with cardiac implantable electronic devices remains controversial, as such masses have been observed in cases of exclusively local infections whereas they have not been recognized in patients with positive cultures of intravascular lead fragments. In this study, we aim to describe the prevalence of intracardiac lead masses in true asymptomatic patients with cardiac implantable electronic devices, to identify their predictive factors and to define their prognostic impact at long-term follow-up. Methods: Seventy-eight consecutive patients admitted over a 6-month period for elective generator replacement without clinical evidence of infection were evaluated by transthoracic and transesophageal echocardiography and prospectively followed at in-clinic follow-up visits. Results: Lead masses were found in 10 patients (12.8%). These patients had more frequently right ventricular dysfunction at univariate analysis (OR 2.71, P  = 0.010) and after baseline variables adjustment (hazard ratio 6.25, P  = 0.012). At 5-year follow-up without any specific therapy, none of the patients suffered from any cardiac device infections, or developed clinical signs of infections. Conclusion: There is an evidence of clinical lead masses in asymptomatic patients with cardiac implantable electronic devices. The value of these findings is still debated for aetiological interpretation and for therapeutic strategy, but they are not necessarily associated with an infection.